2001
DOI: 10.1146/annurev.biophys.30.1.361
|View full text |Cite
|
Sign up to set email alerts
|

Protein Folding Theory: From Lattice to All-Atom Models

Abstract: This review focuses on recent advances in understanding protein folding kinetics in the context of nucleation theory. We present basic concepts such as nucleation, folding nucleus, and transition state ensemble and then discuss recent advances and challenges in theoretical understanding of several key aspects of protein folding kinetics. We cover recent topology-based approaches as well as evolutionary studies and molecular dynamics approaches to determine protein folding nucleus and analyze other aspects of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
259
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 333 publications
(270 citation statements)
references
References 131 publications
9
259
0
Order By: Relevance
“…The collision-first route enables a high basal folding rate of any protein. Mirny and Shakhnovich (2001) reviewed a number of folding kinetics studies and found that in all cases secondary interactions play-at most-a minor role in determining folding kinetics. Instead, strong and Fig.…”
Section: Direct and Indirect Findings Consistent With The Closed Longmentioning
confidence: 99%
See 2 more Smart Citations
“…The collision-first route enables a high basal folding rate of any protein. Mirny and Shakhnovich (2001) reviewed a number of folding kinetics studies and found that in all cases secondary interactions play-at most-a minor role in determining folding kinetics. Instead, strong and Fig.…”
Section: Direct and Indirect Findings Consistent With The Closed Longmentioning
confidence: 99%
“…The nucleation step was suggested to be a mechanism ensuring a fast and efficient folding transition (Wetlaufer 1973;Fersht 1995Fersht , 1997Mirny and Shakhnovich 2001). The nucleus is formed by residues from different parts of the chain, and unstructured loops between them.…”
Section: O'neill Et Al (O'neill and Robert Matthews 2000)mentioning
confidence: 99%
See 1 more Smart Citation
“…The discovery of a class of simple, single-domain proteins which fold via two-state kinetics without any detectable intermediates in the early 1990s [6,7], the development of experimental techniques with improved spatial/temporal resolution [8][9][10][11][12][13], and the application of computer simulations using simplified lattice and off-lattice models [14,15] greatly enhanced our understanding of various aspects of the protein folding problem. Based on the nucleation theory [16][17][18], one of the early proposed mechanisms for protein folding, the nucleation-condensation model was formulated [19][20][21].…”
Section: Studying Protein Foldingmentioning
confidence: 99%
“…They can be seen as a generic formulation of combinatorial optimization problems in computer science and operations research (Garey and Johnson 1979), they describe the Hamiltonians of disordered systems in physics (Binder and Young 1986;Mézard et al 1987;Ferreira et al 2000), and they are (discretized versions of) potential energy surfaces in theoretical chemistry (Mezey 1987). In structural biology, energy landscapes are used to understand the folding of biopolymers into their three-dimensional structures, and discrete versions are used to study folding processes at the level of lattice protein models (Mirny and Shakhnovich 2001) and RNA secondary structures (Flamm and Hofacker 2008).…”
Section: Introductionmentioning
confidence: 99%